What Are the Changes in the Use of Space in The Residential Neighborhood of Residence as A Place of Business? - Isnaeni, Iin; Dewi, Diah Intan Kusumo (Jurnal Teknik Sipil dan Perencanaan, 2018)
Kampung Batik Kauman is the first batik village in Pekalongan where located in the center of Pekalongan.Location and development of Kampung Kauman as batik tourism village has an impact on the physical development, oneof which is marked by the changes of residential house function into a business house. Based on the phenomenon, thepurpose of this paper is to identification space use of business houses in Kampung Batik Kauman. The writer appliedquantitative descriptive method. From the research results can be seen that there are five types of business houses in theKampung Batik Kauman, namely residential houses and batik production; residential houses and batik showrooms;residential houses, production and showroom of batik; residential and boarding houses; and residential houses and tradingand services (except batik). Space utilization of home business in Kampung Kauman consists of the type of utilization ofmixed and separate business house space.